2016
DOI: 10.3920/bm2015.0108
|View full text |Cite
|
Sign up to set email alerts
|

Prophage-mediated modulation of interaction of Streptococcus thermophilus J34 with human intestinal epithelial cells and its competition against human pathogens

Abstract: The human intestinal microbiota plays an important role in human health. While adhesion to gastrointestinal mucosa is a prerequisite for colonisation, inhibition of adhesion is a property which may prevent or reduce infections by food borne pathogens. Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus represent the two lactic bacteria constituting the yoghurt culture. These starter cultures have been claimed to be probiotic. In our study we compared two S. thermophilus strains (i.e. lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Adhesion of S. aureus was the most efficiently inhibited in the exclusion assay (50%), whereas L. monocytogenes was inhibited at the level of 42%. These results showed that probiotic strains can play an important role in the protection of the human gastrointestinal tract against invasion of pathogenic bacteria [91].…”
Section: Prophages As Modulators Of Gut Microbiotamentioning
confidence: 80%
See 1 more Smart Citation
“…Adhesion of S. aureus was the most efficiently inhibited in the exclusion assay (50%), whereas L. monocytogenes was inhibited at the level of 42%. These results showed that probiotic strains can play an important role in the protection of the human gastrointestinal tract against invasion of pathogenic bacteria [91].…”
Section: Prophages As Modulators Of Gut Microbiotamentioning
confidence: 80%
“…It was found that adhesion of pathogenic bacterial strains to human HT29 cells was reduced after administration of the probiotic, lysogenic strain of S. thermophilus J34. This suggests that probiotic strains with prophages may have beneficial effects in the human gastrointestinal tract [91]. It is estimated that over 3% of the bifidobacterial genome consists of bifidoprophages [92][93][94].…”
Section: Prophages As Modulators Of Gut Microbiotamentioning
confidence: 99%
“…The interference of phages with probiotic mechanisms of action was illustrated by a study in which a prophage-cured derivative of S. thermophilus was found to be less effective when competing with pathogenic bacteria (Salmonella, Listeria and Staphylococcus aureus) for adhesion on HT29 epithelial cells as compared to a prophage-containing strain (Guigas et al, 2016), emphasising the importance of checking if probiotic traits remain in cured strains.…”
Section: Management Of Stress Through the Gutmentioning
confidence: 99%
“…Although survival of probiotics in the human gut involves resistance to main GI stresses, capacity to adhere to intestinal epithelial cells may also contribute to their persistence in the GI tract by promoting a transient intestinal colonization [ 11 , 12 ]. In vitro studies have shown that few strains of S. thermophilus , especially the LMD-9 reference strain, are able to adhere to several types of human intestinal epithelial cell lines [ 13 , 14 , 15 , 16 ]. Regarding health effects, in vitro studies and in vivo experiments in rodents have shown that S. thermophilus possesses interesting properties (in addition to lactose digestion improvement) such as prevention of chronic gastritis and antimicrobial or antioxidant activities, as reviewed by Uriot et al [ 17 ].…”
Section: Introductionmentioning
confidence: 99%